Tathbîqu Manhaji al-Dirâsî al-Lughah al-‘Arabiyah ‘ala Asãsi Ma’ayîri al-Ithãri al-Ta’hilî al-Indonîsiyyi (IQF) bi al-Jãmi’ah al-Islãmiyah al-Hukûmiyah Pamekasan Madura - Habibur Rahman (OKARA: Jurnal Bahasa dan Sastra, 2019)
The Curriculum of a college that based on the Indonesian National Qualifications Framework (IQF) is attempting to equate aspects of knowledge, expertise, and skills with achievement in the process of education, job training or experience at a certain level. This research tried to describe and analyze how the IQF based Curriculum implementation at the Arabic Teaching and Learning Department in the State Islamic College (STAIN) Pamekasan Madura. This was a qualitative approach with a case study research. This study revealed that: first, the planning process of the IQF based curriculum implementation at the Arabic Teaching and Learning Department in STAIN Pamekasan is in accordance with the implementation guidelines of the IQF based curriculum from the Research, Technology and Higher Education Ministry. Second, the obstacles in IQF based curriculum implementation were: time, human resource, changes in courses that are not compatible with Arabic education programs, changes in the academic system, language constraints, and lack of intensive socialization. Third, the suggested solution to resolve the obstacles were by revitalizing the design of curriculum, adjusting the vision and mission, reinforce learning outcomes, graduate profile, the structure of the curriculum and providing intensive socialization of curriculum implementation to lecturers and students directly and indirectly.